Pure Science dalam Wacana Tafsir ‘Ilmi Dan I’jaz ‘Ilmi - Erlina, Lira; Saputra, Adha (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
This paper aims to compare the methodology of tafsir ‘ilmi and I'jaz ilmi on verses related to pure science. Pure science calcification includes natural sciences such as physics, biology, chemistry, mathematics. So the problem under study is the pure sciences or what is known as pure science in two discourses; discourse tafsir ‘ilmi and discourse I'jaz ilmi. From the results of the study, it was found that there was a fundamental difference between the methodology of tafsir ‘ilmi and the methodology of I'jaz ilmi which resulted in two different conclusions. In the discourse of tafsir ‘ilmi research on science, the methodology starts from understanding the kauniyah verses related to science and then connected with science without ensuring the authenticity of the ilmiyah theory concluded so that the results of science studies in tafsir 'ilmi still need to be proven true. In contrast to the methodology of I'jaz Ilmi which began from research on ilmiyah theory which was experimentally proven then the truth was preached by the Qur'an.